LISTENING SKILL OF SMA NEGERI 1 MAJENE BY USING SHORT FILM MATERIAL - Ahmad, Munawir; Ridwan, Ridwan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This research was using CAR (Classroom Action Research) method in the teaching process. The objective of this research was to find out and collect the complete data of improvement in the listening skill of application of short film materials. The total number of population of second year was 139 students. There were 10 students as sample of research, they were from class IPA 1, IPA 2, IPA 3, IPA 4 and IPS 1 who joined interest based class as vocational interest academy of Curriculum 2013. The instruments are used to collect the data was multiple choice tests taken from the English subtitle of short films. The multiple choice tests were used to identify what kind of difficulties students face when they are listening. This research was conducted in the cycle 1.Â  After the data had been collected, it was found that the average mean scores of test 1 and test 2 were 5.80 and 6.60 with standard error of mean were 0.29 and 0.45 respectively. Median score of test 1 and test 2 were 5.50 and 6.33 respectively. The items are prone to innormal distributing of the data by looking at the standard deviation of test 1 and test 2. The variance score indicated that the data score of test 2 (2.044) was more variance than the data score of test 1 (0.844). skewness score of test 1 and test 2 in the cycle 1 which were 0.473 and 0.889 meant many low scores and few high scores. These meant that there were tended significant improvement of listening comprehension from performing test 1 and the test 2.